Answer:
[tex]\large\boxed{\dfrac{1}{4}+-\dfrac{2}{3}=-\dfrac{5}{12}}[/tex]
Step-by-step explanation:
[tex]\dfrac{1}{4}+\left(-\dfrac{2}{3}\right)=\dfrac{1}{4}-\dfrac{2}{3}\\\\\text{You must find the common denominator.}\\\\\text{List of multiples of 3:}\ 0,\ 3,\ 6,\ 9,\ \boxed{12},\ 15,\ ...\\\text{List of multiples of 4:}\ 0,\ 4,\ 8,\ \boxed{12},\ 16,\ ...\\\\\text{The common denominator is}\ \boxeed{12}.\\\\3\cdot4=12\\\\\dfrac{1}{4}=\dfrac{1\cdot3}{4\cdot3}=\dfrac{3}{12}\\\\\dfrac{2}{3}=\dfrac{2\cdot4}{3\cdot4}=\dfrac{8}{12}\\\\\\\dfrac{1}{4}-\dfrac{2}{3}=\dfrac{3}{12}-\dfrac{8}{12}=\dfrac{3-8}{12}=-\dfrac{5}{12}[/tex]